2020
DOI: 10.1088/1757-899x/883/1/012206
|View full text |Cite
|
Sign up to set email alerts
|

The extraction of the water-air phase through a single filtration hole

Abstract: The conducted studies allowed us to establish that the shape of the filtration holes should be subject to the above patterns. The second - it was established on the basis of the analysis of real Reynolds numbers and visual observations that the water extraction mode in the zone of action of the peristaltic wave of compaction is divided into three stages: a) laminar spin mode; b) turbulent spin mode; c) intermittent spin mode. The first stage of water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Further studies conducted by E. N. Shcherbakov have shown that high-strength concretes (grades up to 1000) also obey regularity (1) quite well. This can be seen from the analysis of the data of numerous researchers given in [9][10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies conducted by E. N. Shcherbakov have shown that high-strength concretes (grades up to 1000) also obey regularity (1) quite well. This can be seen from the analysis of the data of numerous researchers given in [9][10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies [24][25][26][27][28][29] have established that the degree of squeezing out excess mixing water during vibration-impact pressing depends on its initial content in concrete, on cement consumption, the initial volume of voids in the mixture, and the intensity of compaction, fig. 1, and the highest compression ratio corresponds to a pressure of 3 to 7 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…The production of high-strength concrete by vibration-impact pressing is achieved by densely filling the intergranular space with cement paste and mortar with a simultaneous displacement of air bubbles, squeezing out part of the free water behind the portions of the compacted mixture [13][14][15][16][17][18][19]. In case of an unsuccessful selection of the composition of the concrete mixture, a rigid, practically incompressible frame of aggregate grains can form [20][21][22][23][24][25][26]. Note: Above the line is test results of concrete samples, compacted; vibro-impact pressing, under the line -the same, compacted by vibration, Where: R bvp is the strength of vibro-impact-peristaltic pressed concrete; R bv is the strength of vibro-compacted concrete.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Using the least amount of raw substrates, while still meeting the required criteria, is significant as it allows for cost-effective processing. Light-emitting diodes, [13] air/water filters, [14] medicine delivery, [15] antireflective coatings, [16] electronic tools, [17] and photovoltaics [18] are just a few examples of thin films. A wide range of advanced technical applications can benefit from the desirable properties of nanocomposite films immobilized with nanomaterials, such as catalysis, [19] and antimicrobial, [20] sensory, [21] water repellency, [22] electrical conductivity, [23] and ultraviolet light protection.…”
Section: Introductionmentioning
confidence: 99%